The impact of halal brand personali̇ty and onli̇ne brand trust on the onli̇ne halal food purchase intenti̇on: a conceptual paper / Musdiana Mohamad Salleh and Etty Harniza Harun - Mohamad Salleh, Musdiana; Harun, Etty Harniza (Universiti Teknologi MARA, Kedah, 2021)
The purpose of this paper is to develop a conceptual framework that provides insight and aids in understanding the factors that determine the intention of consumer to purchase halal food products via an online platform. Online consumer behaviour can be described as the consumer perceives the process involved in ay the the online purchase. Consumers can order and purchase halal food from a diverse range of websites like grocery stores, supermarkets, restaurants, food intermediaries, and delivery businesses. By understanding what makes customers shop online, online retailers can build more trustable, secure, attractive, and useful websites and create the effective marketing programme for their customers. Past researches found the connection between brand personality in relation with food choice. Customers tend to purchase from the online website they trust and brands that are familiar and suitable with their personality. Although the relationship between trust and online purchase intention had been widely discussed, how trust mediates t he relationship between brand personality and online purchase intention remains uncertain. Therefore, trust as a moderating variable is introduced in the conceptual framework to determine if there exists positive behavioural outcomes. The framework aids understanding in the relationships and provides insights into how these relationships develop.